Reasons for continuous sedation until death in cancer patients: a qualitative interview study. (29th October 2015) - Robijn, L.; Chambaere, K.; Raus, K.; Rietjens, J.; Deliens, L.
Abstract : End‐of‐life sedation, though increasingly prevalent and widespread, remains a highly debated medical practice in the context of palliative medicine. This qualitative study aims to look more specifically at how health care workers justify their use of continuous sedation until death and which factors they report as playing a part in the decision‐making process. In‐depth interviews were held with 28 physicians and 22 nurses of 27 cancer patients in Belgium who had received continuous sedation until death in hospitals, palliative care units or at home. Our findings indicate that medical decision‐making for continuous sedation is not only based on clinical indications but also related to morally complex issues such as the social context and the personal characteristics and preferences of individual patient and their relatives. The complex role of non‐clinical factors in palliative sedation decision‐making needs to be further studied to assess which medically or ethically relevant arguments are underlying daily clinical practice. Finally, our findings suggest that in some cases continuous sedation was resorted to as an alternative option at the end of life when euthanasia, a legally regulated option in Belgium, was no longer practically possible.